2022
DOI: 10.1111/jdv.18450
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of dupilumab in the treatment of atopic dermatitis in children (6–11 years): data from a French multicentre retrospective cohort in daily practice

Abstract: Background Dupilumab is the first biotherapy available for the treatment of moderate-to-severe childhood atopic dermatitis (AD).Objective The aim of this study was to evaluate the effectiveness and safety of dupilumab in daily practice.Methods Patients aged 6-11, who had received a first dose of dupilumab, were included in this multicentre retrospective cohort study. The primary endpoint was change in SCORAD after 3 months of treatment. Secondary endpoints were change in IGA score at 3 months, proportion of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
(56 reference statements)
3
8
1
Order By: Relevance
“…Te overall incidence of treatment-emergent adverse events was 7.7% in our pediatric cohorts during the 16-week dupilumab treatment period (Table 3), which was even lower than previous real-world studies in children aged 6-11 years (12.5%), adolescents (13.5%), and adults (17.5%) [14,15,18]. In fact, a larger regimen (Table 3) was partly administrated in our cohorts, which might further prove dupilumab a safe choice in pediatric patients, considering the low occurrence of adverse events.…”
Section: Discussioncontrasting
confidence: 62%
“…Te overall incidence of treatment-emergent adverse events was 7.7% in our pediatric cohorts during the 16-week dupilumab treatment period (Table 3), which was even lower than previous real-world studies in children aged 6-11 years (12.5%), adolescents (13.5%), and adults (17.5%) [14,15,18]. In fact, a larger regimen (Table 3) was partly administrated in our cohorts, which might further prove dupilumab a safe choice in pediatric patients, considering the low occurrence of adverse events.…”
Section: Discussioncontrasting
confidence: 62%
“…Moreover, AEs led to treatment discontinuation in three (3.8%) patients. No serious AEs were collected [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment groups received dupilumab monotherapy in two trials 12,13 , while the other two by Paller et al and Yang et al included patients applying concomitant TCs. 14,15 Measures used to assess disease severity in these studies included the Eczema Area Severity index (EASI), SCORing Atopic Dermatitis (SCORAD), and Investigator's Global Assessment (IGA). Three of the studies included patient reported outcomes such as the Dermatology Life Quality Index (DLQI) and the Pruritic Numeric Rating Scale for itch (P-NRS).…”
Section: Resultsmentioning
confidence: 99%
“…By reducing pruritic skin lesions, dupilumab resulted in improved quality of life for these children as measured through c-DLQI. 11,12,14,15 Of the studies included, no patients discontinued dupilumab due to severe treatment-emergent adverse events (TEAEs) related to dupilumab. Most prevalent side effects included conjunctivitis, nasopharyngitis, headaches, and injection-site reaction.…”
Section: Discussionmentioning
confidence: 99%